2016
DOI: 10.1089/ast.2015.1418
|View full text |Cite
|
Sign up to set email alerts
|

A New Empirical Constraint on the Prevalence of Technological Species in the Universe

Abstract: In this paper we address the cosmic frequency of technological species.Recent advances in exoplanet studies provide strong constraints on all astrophysical terms in the Drake Equation. Using these and modifying the form and intent of the Drake equation we show that we can set a firm lower bound on the probability that one or more additional technological species have evolved anywhere and at any time in the history of the observable Universe. We find that as long as the probability that a habitable zone planet … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 9 publications
0
31
0
Order By: Relevance
“…Soon after, von Hoerner, Shklovskii, and Sagan (von Hoerner 1961) (Shklovskii & Sagan 1966) concluded that the equation's precision depended principally on its parameter L -the mean lifetime of a communicating civilization -because L's value was uncertain over several orders of magnitude. While subsequent advances in astrophysics have improved the precision of several parameters in the Drake equation (Burchell 2006) (Frank & Sullivan 2016) (Vakoch & Dowd 2015), L remains highly uncertain (Oliver & Billingham 1971) (Ambartsumian & Sagan 1973) (Billingham et al 1979) (Duncan 1991) (Schenkel 1999) (Kompanichenko 2000) (Rubin 2001) (Forgan 2009) (Maccone 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Soon after, von Hoerner, Shklovskii, and Sagan (von Hoerner 1961) (Shklovskii & Sagan 1966) concluded that the equation's precision depended principally on its parameter L -the mean lifetime of a communicating civilization -because L's value was uncertain over several orders of magnitude. While subsequent advances in astrophysics have improved the precision of several parameters in the Drake equation (Burchell 2006) (Frank & Sullivan 2016) (Vakoch & Dowd 2015), L remains highly uncertain (Oliver & Billingham 1971) (Ambartsumian & Sagan 1973) (Billingham et al 1979) (Duncan 1991) (Schenkel 1999) (Kompanichenko 2000) (Rubin 2001) (Forgan 2009) (Maccone 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the assumptions made about the lifetime of technological civilizations, Frank and Sullivan calculated the number of civilizations that could have existed to be on the order of tens of thousands to a trillion civilizations that could have appeared over cosmic history. 77,78 American Institute of Aeronautics and Astronautics…”
Section: Discussionmentioning
confidence: 99%
“…Many estimates have been made of the number of extraterrestrial civilizations using approaches such as the Drake equation. These estimates vary considerably according to the many assumptions made, and range from millions to zero (for example, Drake and Sobel 1992;Wilson 2001;Forgan 2009;Frank and Sullivan 2016;Sandberg et al 2018). Considerations include whether the estimates apply to the Milky Way or the observable universe, include past and future civilizations, and whether communication constraints such as the speed of light are considered.…”
Section: Advanced Civilizations In Universes and Multiversesmentioning
confidence: 99%